Analyzing the Turkish House with Respect to Flexibility Strategies - İslamoğlu, Özge; USTA, GÜLAY (My University, 2017)
The semantic and spatial continuity of the traditional Turkish house is a significant issue for cultural continuity. At modern sustainability studies on traditional Turkish house, it can be seen that these approaches essentially focus on facade level merely whereas the reality dictates that traditional Turkish houses possess a myriad of semantic values and design principles that need to be adapted to the modern housing design. Only if the principles that suit to modern conditions continue then can it be viable to ensure sustainability. Flexibility stands out as one of the most crucial principles in sustainability. Schneider and Till (2007) argues that “by acknowledging change as an underlying parameter but accepting the level and extent of change as unknown, flexible housing is inherently sustainable”. Also, Broome (2005) regards flexibility as part of sustainable system. Within the context of this study flexibility concept that refers to a major design approach in the spatial organization of a Turkish house has been analyzed. Spatial and functional organization of a Turkish house has been analyzed with respect to the strategies created within flexibility context. On the basis of obtained findings, suggestions that could provide data for modern housing designs have been offered.
Keywords: Esneklik; türk konutunda esneklik; Flexibility; Flexibility Strategies; Traditional Turkish house; Spatial and functional analysis